Statistical energy analysis applied to structure-borne noise in computer equipment - Yap, Fook Fah. (2008)
Analysis of structure-borne noise in computers and peripherals such as hard disk drives and printed circuit boards. Development of analysis and optimum design modification technique by Statistical Energy Analysis.